2019
DOI: 10.1371/journal.pone.0225852
|View full text |Cite
|
Sign up to set email alerts
|

The effects of urbanization on bee communities depends on floral resource availability and bee functional traits

Abstract: Wild bees are important pollinators in many ecosystems threatened by anthropogenic disturbance. Urban development can reduce and degrade natural habitat for bees and other pollinators. However, some researchers suggest that cities could also provide refuge for bees, given that agricultural intensification may pose a greater risk. In this study, we surveyed bee communities at 15 farms and gardens across an urban-rural gradient in southeastern Michigan, USA to evaluate the effect of urbanization on bees. We exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 87 publications
2
73
1
Order By: Relevance
“…Regarding the elevated diversity of pollen forage observed at urban sites, it is important not to jump to the interpretation that our more urban sites were more suitable for honeybees than the agricultural sites. To the contrary, prior studies in this region found that urban land use was negatively associated with colony productivity for both honeybees (Sponsler & Johnson, 2015) and bumblebees (Milano et al., 2019; Wilson & Jamieson, 2019) and that honeybee colonies situated at the agricultural–suburban divide (site CC) dedicated significantly more foraging activity towards rural agricultural land cover components during the 2014 season of this study (Sponsler et al., 2017). While Ohio urban land cover apparently contains a diverse floral assemblage, a trait which potentially makes it amenable to generalist solitary bees and certain bumblebee species (Baldock et al., 2019; Samuelson et al., 2018), it may be depauperate in the high‐volume floral resource patches which drive honeybee colony growth.…”
Section: Discussioncontrasting
confidence: 81%
“…Regarding the elevated diversity of pollen forage observed at urban sites, it is important not to jump to the interpretation that our more urban sites were more suitable for honeybees than the agricultural sites. To the contrary, prior studies in this region found that urban land use was negatively associated with colony productivity for both honeybees (Sponsler & Johnson, 2015) and bumblebees (Milano et al., 2019; Wilson & Jamieson, 2019) and that honeybee colonies situated at the agricultural–suburban divide (site CC) dedicated significantly more foraging activity towards rural agricultural land cover components during the 2014 season of this study (Sponsler et al., 2017). While Ohio urban land cover apparently contains a diverse floral assemblage, a trait which potentially makes it amenable to generalist solitary bees and certain bumblebee species (Baldock et al., 2019; Samuelson et al., 2018), it may be depauperate in the high‐volume floral resource patches which drive honeybee colony growth.…”
Section: Discussioncontrasting
confidence: 81%
“…In line with the results of the present study, other studies have documented higher numbers of cavitynesting bees in urban areas (Kearns and Oliveras, 2009;Sirohi et al, 2015;Husmann et al, 2016) than in natural habitats. Diversity studies conducted in green spaces in cities (Frankie et al, 2009), on urban green roofs (Colla et al, 2009) and in semi-urban areas (Seller and Hicks, 2015;Wilson and Jamieson, 2019), have shown Lasioglossum (Choate et al, 2018) and Halictus to be the common species of solitary bees in urban areas, as reported in the present study as well. Together, these studies confirm that cavity-nesting social and solitary bees are better adapted to urban habitats because those bees are able to nest in built structures and also represent adequate diversity in their species composition in such habitats.…”
Section: Resultssupporting
confidence: 86%
“…One functional group of interest for protection are native pollinators which are integral to sustaining agricultural food systems ( IPBES, 2016 ) and may play important functional roles in urban settings ( Hall et al, 2017 ). Urban and suburban landscapes have the potential to protect and enhance wild bee diversity and abundances ( Pardee & Philpott, 2014 ; Baldock et al, 2015 ; Baldock et al, 2019 ; Lowenstein, Matteson & Minor, 2015 ; Wilson & Jamieson, 2019 ; Wenzel et al, 2020 ) via careful policy development ( Hall & Steiner, 2019 ) and promotion of pollinator friendly behaviors among the urban public ( Hall et al, 2017 ; Zattara & Aizen, 2019 ; Cardoso et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%